1987
DOI: 10.1007/bf02636388
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic considerations of polymorphic transformations of tristearin in the presence of emulsifiers

Abstract: Fat polymorphs influence the quality of some food and cosmetic products. Emulsifiers traditionally have been added in order to retard undesired polymorphic transformations. The present study is an attempt to understand the role of selected emulsifiers on such transformations. Tristearin was heated or aged under controlled conditions using differential scanning calorimetry (DSC) and X‐ray techniques, and the extent of transformation was evaluated in view of the possible pathways of α transforming into β. The te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…To explain these observations it should be realized that the transformation involves the transition from a loosely packed α-modification to a tightly packed -modification. Such transitions will be hindered by the presence of foreign compounds, acting as crystal structure modifiers or as retarders of polymorphic transformations (18). It is further observed that increasing amounts of phospholipid affect the hardness of the final coagel ( Table 1).…”
Section: Effects Of Other Surfactantsmentioning
confidence: 96%
“…To explain these observations it should be realized that the transformation involves the transition from a loosely packed α-modification to a tightly packed -modification. Such transitions will be hindered by the presence of foreign compounds, acting as crystal structure modifiers or as retarders of polymorphic transformations (18). It is further observed that increasing amounts of phospholipid affect the hardness of the final coagel ( Table 1).…”
Section: Effects Of Other Surfactantsmentioning
confidence: 96%
“…Bowser [12] showed that the addition of PGPR or standard soy lecithin to cocoa butter produces numerous crystals of small sizes or few crystals of larger size, respectively. In general, the effect of emulsifiers on fat is associated to the development of different crystalline organizations and/or imperfections [13]. Two different mechanisms have been reported in order to interpret the influence of emulsifiers on fats crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Some emulsifiers can delay transformations via steric hindrance, while others lead to these transformations, thus favoring polymorphic transitions. [6] Two different procedures have been reported in the literature to analyze the effect of emulsifiers on fat crystallization. The first mechanism describes the action of these additives as heteronuclei, whereby the crystallization is accelerated by direct catalytic action as impurities.…”
Section: Introductionmentioning
confidence: 99%